2019
DOI: 10.1021/acsbiomaterials.8b01609
|View full text |Cite
|
Sign up to set email alerts
|

Human Hair Keratin Hydrogels Alleviate Rebleeding after Intracerebral Hemorrhage in a Rat Model

Abstract: Surgery is an important therapeutic strategy for intracerebral hemorrhage (ICH) in the clinic and is theoretically beneficial for the outcome of ICH by decreasing hematoma, reducing nervous tissue damage, and removing harmful chemicals. However, the outcome of ICH surgery is always unsatisfactory due to postoperative rebleeding. We hypothesized that the injection of hemostatic agents in situ after aspiration surgery could immediately activate hemostasis once rebleeding occurs. Therefore, keratin hydrogels (K-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Numerous natural and synthetic biomaterials, such as fibrin, gelatin, HA, , HA and methylcellulose (HAMC), silk fibroin, , keratin, RGD-containing elastin-like polypeptide (REP), Pluronic F127, and poly­( N -isopropylacrylamide), have been exploited to build hydrogel platforms for CNS repair. These hydrogels were designed with injectability, thermo-sensitivity, or composite formula.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Numerous natural and synthetic biomaterials, such as fibrin, gelatin, HA, , HA and methylcellulose (HAMC), silk fibroin, , keratin, RGD-containing elastin-like polypeptide (REP), Pluronic F127, and poly­( N -isopropylacrylamide), have been exploited to build hydrogel platforms for CNS repair. These hydrogels were designed with injectability, thermo-sensitivity, or composite formula.…”
Section: Discussionmentioning
confidence: 94%
“…These hydrogels were designed with injectability, thermo-sensitivity, or composite formula. Preparation of the HAMC hydrogel started from blending HA and MC solutions, where the hydrogel underwent a sol–gel transition after an increase of temperature based on physical interactions. , The keratin hydrogels were produced from keratin solutions through a long oxidation process by covalent cross-linking. , In this study, CS hydrogels were readily and rapidly prepared by mixing glycol chitosan and DF-PEG solutions via dynamic imine bonds. Moreover, CS hydrogels exhibited the increase of stiffness with the temperature raised from 25 to 37 °C .…”
Section: Discussionmentioning
confidence: 99%
“…High apoptosis rates have been observed in the renal tubular epithelial cells of rats with UA-induced kidney disease ( 26 ). Increasing evidence shows that apoptosis could serve as a therapeutic paradigm in hyperuricemia ( 27 ). Yang et al ( 28 ) found that renal tubular epithelial cell apoptosis occurs in rats with UA-induced kidney disease and the use of the antioxidant glutathione can inhibit cell apoptosis significantly and reduce kidney damage.…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting work, He et al fabricated hemostatic keratin hydrogels (K-gels) via a rehydration method from human hair keratin extracts and its therapeutic effects in the treatment of ICH rebleeding was assessed in rat brain in vivo (Figure 7). [73] To prepare the K-gels at different concentrations (30,35, and 40% (w/v)), ultrapure water was used to reconstitute the lyophilized keratin powders. The homogeneous distribution was achieved through vigorously mixing the mixture by vortexing followed by stirring at 37°C to crosslink and form the gels.…”
Section: Keratinmentioning
confidence: 99%
“…Reproduced with permission. [73] Copyright 2019, American Chemical Society. Reproduced with permission.…”
Section: Silkmentioning
confidence: 99%